GLOBAL UNCERTAINTY AND UNEMPLOYMENT RATE IN THE UK AND NIGERIA: TRIGGER OF REGIME CHANGE AND ITS IMPLICATIONS FOR POLICY ANALYSIS - Oderinde, Lukmon; Sanusi, Gbenga; Ajayi, Babajide; Atoloye-Kayode, Remi; Agbawn, Mathew; Ihuarulam, Gideon (The European Journal of Applied Economics, 2024)
This study applies a threshold regression model to explore the impact of uncertainty on unemployment in Nigeria and United Kingdom with data from 1970 to 2021. The empirical results show a significant threshold effect of uncertainty on unemployment. The threshold effect estimated value of global uncertainty on unemployment is significantly higher in Nigeria than in the UK. The trigger estimated value for Nigeria and the UK are 0.421 and 0.093 respectively. However, the impact differs in magnitude. While below the threshold value of 0.093, the impact is higher in the UK than in Nigeria, but the reverse holds beyond this threshold. This presupposes the role and impact of sturdy policy formulation and implementation between the two countries. Unemployment rate is lower in the UK than in Nigeria. Finally, the relationship between global uncertainty and unemployment is linear for Nigeria and positive. However, a non-linear and inverted U-shape relationship was confirmed for the UK. It becomes imperative to build world uncertainty into government future policies formulation if the impacts of vagaries of uncertainty on macroeconomic stability and business cycle fluctuations would be mitigated.
Keywords: Unemployment rates, Economic fluctuations, Nigeria, United Kingdom